2009
DOI: 10.1186/1755-8794-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile analysis of human hepatocellular carcinoma using SAGE and LongSAGE

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and the second cancer killer in China. The initiation and malignant transformation of cancer result from accumulation of genetic changes in the sequences or expression level of cancer-related genes. It is of particular importance to determine gene expression profiles of cancers on a global scale. SAGE and LongSAGE have been developed for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…Highly up-regulated (up to 44-fold change) in the Pak1-KO MEFs are Pdlim1 gene PDZ - LIM domain 1 and Sgce gene (sarcoglycan-epsilon) which encodes the epsilon member of the sarcoglycan family . Both PDLIM1 and SGCE are known to play role in human cancers and cytoskeleton signaling [17] [18] [19] [20]. SGCE is a member of transmembrane proteins, which acts as a link between actin cytoskeleton and the extra cellular matrix and is also implicated in neuronal disorder such as myoclonus-dystonia syndrome .…”
Section: Resultsmentioning
confidence: 99%
“…Highly up-regulated (up to 44-fold change) in the Pak1-KO MEFs are Pdlim1 gene PDZ - LIM domain 1 and Sgce gene (sarcoglycan-epsilon) which encodes the epsilon member of the sarcoglycan family . Both PDLIM1 and SGCE are known to play role in human cancers and cytoskeleton signaling [17] [18] [19] [20]. SGCE is a member of transmembrane proteins, which acts as a link between actin cytoskeleton and the extra cellular matrix and is also implicated in neuronal disorder such as myoclonus-dystonia syndrome .…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no known published reports of porcine SGCE isoforms, nine possible isoforms have been predicted by genome annotation in the mouse, and four in humans [46]. Recently, it has been reported that SGCE is upregulated in human hepatocellular carcinoma [55], suggesting that SGCE plays a role in hepatocyte proliferation. Thus, it is plausible that maternal expression of the usually silent allele, leading to a relative increase in SGCE levels, is a compensatory mechanism present at a developmental time of very rapid liver growth.…”
Section: Identification Of Tissue-specific Imprintingmentioning
confidence: 99%
“…However its involvement in cancer is not clear. Dong et al (29) defined an expression profile for human hepatocarcinoma. In this assay they showed that SGCE was overexpressed in these tumours in comparison with non-tumour liver.…”
Section: Discussionmentioning
confidence: 99%